Slave Revolt on Screen: the Haitian Revolution in Film and Video Games - Sepinwall, Alyssa Goldstein (University Press of Mississippi, 2021)
In Slave Revolt on Screen: The Haitian Revolution in Film and Video Games author Alyssa Goldstein Sepinwall analyzes how films and video games from around the world have depicted slave revolt, focusing on the Haitian Revolution (1791–1804). This event, the first successful revolution by enslaved people in modern history, sent shock waves throughout the Atlantic World. Regardless of its historical significance however, this revolution has become less well-known—and appears less often on screen—than most other revolutions; its story, involving enslaved Africans liberating themselves through violence, does not match the suffering-slaves-waiting-for-a-white-hero genre that pervades Hollywood treatments of Black history. Despite Hollywood’s near-silence on this event, some films on the Revolution do exist—from directors in Haiti, the US, France, and elsewhere. Slave Revolt on Screen offers the first-ever comprehensive analysis of Haitian Revolution cinema, including completed films and planned projects that were never made. In addition to studying cinema, this book also breaks ground in examining video games, a pop-culture form long neglected by historians. Sepinwall scrutinizes video game depictions of Haitian slave revolt that appear in games like the Assassin’s Creed series that have reached millions more players than comparable films. In analyzing films and games on the revolution, Slave Revolt on Screen calls attention to the ways that economic legacies of slavery and colonialism warp pop-culture portrayals of the past and leave audiences with distorted understandings.
Section: vi, 339 pages : illustrations ; 24 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Femmes et violence de masse. - Myre, Nadia; Uzel, Jean-Philippe (Spirale, 2018)
"Si tous les groupes humains sont touchés par la violence à grande échelle, les femmes la subissent sous des formes spécifiques, comme en témoignent les assassinats systémiques des femmes et des filles autochtones en Amérique du Nord et en Amérique latine, ou encore les nombreux conflits armés (Syrie, Lybie, Birmanie, entre autres) dans lesquels le viol est érigé en arme de guerre. Les deux phénomènes peuvent d'ailleurs se recouper puisque l'un des tout premiers féminicides à avoir été qualifié et documenté comme tel en Amérique est celui ayant été perpétré contre les femmes mayas durant la guerre civile guatémaltèque au début des années 1980. Cependant, les femmes ne sont pas seulement les victimes de la violence de masse, puisqu'elles sont aussi les premières à témoigner et dénoncer pour faire barrage à cette violence. Ce numéro hors-série regroupe des articles et des projets visuels qui décrivent et analysent la violence de masse liée au genre. Il s'agit de réfléchir sur la manière de représenter cette violence et d'en témoigner, d'autant plus qu'elle est bien souvent rendue invisible et inaudible par le patriarcat, le colonialisme, les intérêts politiques en présence ou l'impéritie de l'État."
Section: 89 pages : illustrations en couleur ; 26 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Teresa Margolles: mundos - Margolles, Teresa; Uzel, Jean-Philippe; Garcia, Emeren; Zeppetelli, John; St-Gelais, Thérèse; Morales, Lourdes (Musée d'art contemporain de Montréal, 2017)
Violence and the dead are major thematics in the sociopolitical art of Teresa Margolles. Born in Culiacan, Mexico, Margolles unfalteringly exposes the social causes and consequences of the endemic violence that ravages her country: violent deaths from the drug trade, exclusions, feminicides, and social injustice. Many of her works consist of substances or objects that have been in close contact to violent crimes and dead bodies, such as water with which corpses have been cleaned, blood-soaked earth, or fabric drenched in body fluids. This monograph brings together works from the past decade, along with pieces that have never been shown before, including sculptural and photographic installations, performative interventions and videos. Spare, yet powerfully moving, Margolles's work reaches out and brings the viewer into the world of those whose lives have been made invisible.
Section: 118 pages : illustrations (some color) ; 25 cm
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Oubliées ou disparues : Matérialiser absences et mémoires - Graff, Julie (ICOFOM Study Series, 2020)
L’exposition Öndia’tahterendih, oubliées ou disparues : Akonessen, Zitya, Marie et les autres, créée par la Boite Rouge Vif, une OBNL autochtone du Québec, et la commissaire wendate Sylvie Paré, présente 10 artistes rendant hommage aux femmes et aux filles autochtones touchées par le féminicide autochtone, tout en cherchant à mobiliser le public. Je souhaite dans le cadre de cet article explorer les stratégies mises en place au sein de l’exposition, telle qu’elle a été présentée au musée de la Civilisation du Québec en 2018. Je conclurai en explorant l’inscription de l’exposition dans le développement d’un commissariat engagé autochtone au Canada.
ISBN: 9782491997113 Number: 48-1
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Absorbing or Obscuring the Absence of a Critical Space in the Americas for Indigeneity: The Smithsonian's National Museum of the American Indian - Rickard, Jolene (Res: Anthropology and Aesthetics, 2007)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; _Nettoyé

Épistémologies du Sud, pensées et féminismes décoloniaux latino-américains - Coenga-Oliveira, Danielle (Revue Possibles, 2019)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

El color de la razón: racismo epistemológico y razón imperial - Castro-Gómez, Santiago; Eze, Emmanuel Chukwudi; Henry, Paget (Ediciones del Signo, 2014)
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Section: 271 pages : illustrations en couleur ; 25 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Le jardin en ville, le cas des Jardins éphémères à Québec. Stratégie marchande et critique postcoloniale - Pageot, Édith-Anne (Globe, 2012)
Cet article se penche sur la portée philosophique du projet intitulé Jardins éphémères, un ensemble de onze jardins temporaires réalisés dans le cadre des activités visant à célébrer le 400ₑ anniversaire de la fondation de la ville de Québec au cours de l’été 2008. L’organisation, les intentions et les principaux thèmes sous-jacents aux différents projets sont présentés dans leur ensemble. Le jardin intitulé « Wampum 400 », créé par deux artistes autochtones, Domingo Cisneros et Sonia Robertson Piekuakamilnu, fait l’objet d’un commentaire plus long. L’analyse montre que le projet Jardins éphémères dans son ensemble incarnait les principaux enjeux actuels du jardin en ville. Certains aspects reconduisaient la vision idéelle du jardin, d’autres satisfaisaient la logique touristique de l’événement et d’autres, enfin, développaient une position critique qui concerne la réappropriation d’un espace à usage collectif et, du coup, interrogeaient les fondements épistémologiques et ontologiques du « jardin ».
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas–from Nunavut to Tierra del Fuego. Through three themes–landscape, territory, and trade–this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."–Résumé de l'éditeur
Section: 223 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Flora and Fauna Otherwise: Black and Brown Aesthetics of Relation in Firelei Báez and Wangechi Mutu - Alvarado, Leticia (Latin American and Latinx Visual Culture, 2019)
Pairing Dominican-born artist Firelei Báez with Kenyan-born artist Wangechi Mutu, this article meditates on relational black and brown aesthetic strategies by reading femme gestures performatively across individual works, as well as the exhibition spaces within which the artists draft practices of informed and resistant engagement. Working with both theories of brownness that emerge from Latinx studies as well as scholarship of the black radical tradition, the author follows a sense of shared aesthetic gestures in Báez and Mutu’s work toward an indictment of pervasive Global North racial epistemologies. Focusing on the performative gesture as the basis for relation, this article ultimately hones in on the chimeric figures—amalgamations of flora and fauna—that both artists deploy, arguing that these present a model for imagining an otherwise arrangement of the social.R Poniendo en diálogo a Firelei Báez, una artista nacida en República Dominicana, con Wangechi Mutu, que nació en Kenia, este artículo invita a una meditación sobre las estrategias estéticas relacionales negras y morenas mediante una lectura en clave performativa de gestos femeninos en obras individuales y en aquellos espacios de exposición en que las artistas elaboran prácticas de participación política informada y de resistencia. Trabajando tanto con las teorías de lo moreno (brownness) que emergen de los estudios Latinx como con el trabajo académico de la tradición radical negra, la autora rastrea gestos estéticos presentes tanto en el trabajo de Báez como en el de Mutu para denunciar las omnipresentes epistemologías raciales del norte global. Centrándose en el gesto performativo como la base de la relación, este artículo se enfoca en última instancia en las figuras quiméricas – amalgamaciones de flora y fauna – que ambas artistas despliegan en su trabajo para sostener que estas presentan un modelo para imaginar otra manera de organizar lo social.
Keywords: 1-Histoire de l'art; 2-Analyses formalistes; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Visual Disobedience: The Geopolitics of Experimental Art in Central America, 1990-Present - Cornejo, Kency (N.D., 2014)
This dissertation centers on the relationship between art and politics in postwar Central America as materialized in the specific issues of racial and gendered violence that derive from the region's geopolitical location and history. It argues that the decade of the 1990s marks a moment of change in the region's cultural infrastructure, both institutionally and conceptually, in which artists seek a new visual language of experimental art practices to articulate and conceptualize a critical understanding of place, experience and knowledge. It posits that visual and conceptual manifestations of violence in Central American performance, conceptual art and installation extend beyond a critique of the state, and beyond the scope of political parties in perpetuating violent circumstances in these countries. It argues that instead artists use experimental practices in art to locate manifestations of racial violence in an historical system of domination and as a legacy of colonialism still witnessed, lived, and learned by multiple subjectivities in the region. In this postwar period artists move beyond the cold-war rhetoric of the previous decades and instead root the current social and political injustices in what Aníbal Quijano calls the `coloniality of power.' Through an engagement of decolonial methodologies, this dissertation challenges the label "political art" in Central America and offers what I call "visual disobedience" as a response to the coloniality of seeing. I posit that visual colonization is yet another aspect of the coloniality of power and indispensable to projects of decolonization. It offers an analysis of various works to show how visual disobedience responds specifically to racial and gender violence and the equally violent colonization of visuality in Mesoamerica. Such geopolitical critiques through art unmask themes specific to life and identity in contemporary Central America, from indigenous genocide, femicide, transnational gangs, to mass imprisonments and a new wave of social cleansing. I propose that Central American artists–beyond an anti-colonial stance–are engaging in visual disobedience so as to construct decolonial epistemologies in art, through art, and as art as decolonial gestures for healing.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Representations of Whiteness in the Black Imagination - hooks, bell (Belonging: A Culture of Place, 2019)
Searching the critical work of post-colonial critics, the author found much writing that bespeaks the continued fascination with the way white minds, particularly the colonial imperialist traveler, perceive blackness, and very little expressed interest in representations of whiteness in the black imagination. Some white people may even imagine there is no representation of whiteness in the black imagination, especially one that is based on concrete observation or mythic conjecture. Stereotypes black folks maintain about white folks are not the only representations of whiteness in the black imagination. Yet it is this representation of whiteness in the black imagination, first learned in the narrow confines of poor black rural community, that is sustained by the author travels to many different locations. Theorizing diverse journeying is crucial to the people understanding of any politics of location.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé

Interview with author, Dr. Laura Pérez - Ramirez, Abraham
Interview with author, Dr. Laura Pérez, Professor of Ethnic Studies at UC Berkeley on her most recent book, Eros Ideologies: Writings on Art, Sprituality, & the Decolonial.
Related with the book "Eros ideologies. Writings on art, spirituality, and the decolonial" of Laura Pérez
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Eros ideologies. Writings on art, spirituality, and the decolonial. - Perez, Laura E (Duke University Press, 2019)
In 'Eros Ideologies' Laura E. Perez explores the decolonial through Western and non-Western thought concerning personal and social well-being. Drawing upon Jungian, people-of-color, and spiritual psychology alongside non-Western spiritual philosophies of the interdependence of all life-forms, she writes of the decolonial as an ongoing project rooted in love as an ideology to frame respectful coexistence of social and cultural diversity. In readings of art that includes self-portraits by Frida Kahlo, Ana Mendieta, and Yreina D. Cervantez, the drawings and paintings of Chilean American artist Liliana Wilson, and Favianna Rodriguez's screen-printed images, Perez identifies art as one of the most valuable laboratories for creating, imagining, and experiencing new forms of decolonial thought. Such art expresses what Perez calls eros ideologies: understandings of social and natural reality that foreground the centrality of respect and care of self and others as the basis for a more democratic and responsible present and future. Employing a range of writing styles and voices-from the poetic to the scholarly-Perez shows how art can point to more just and loving ways of being.
Related with the Podcast "Interview with author, Dr. Laura Pérez"
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

Revista N'oj Panel on Decolonizing Aesthetics - Latinx Research Center (2020)
The Latinx Research Center's Revista N'oj hosted a round table discussion on Decolonial Aesthetics titled, "Decolonizing Art & Praxis in the Time of Covid-19." The talk included Jesus Barraza, Dr. Guisela Latorre, Dr. Mauricio Barros de Castro, and Dr. Laura E. Pérez. The panel was moderated by Revista N'oj editor, Abraham Ramirez.
Revista N'oj : Issue No.2 (2020) Event was sponsored by the Latinx Research Center at the University of California, Berkeley
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Race and Media: Critical Approaches - Lopez, Lori Kido (New York University Press, 2020)
1. Racism and Mainstream Media / Lori Kido Lopez – 2. Image Analysis and Televisual Latinos / Mary Beltrán – 3. Visualizing Mixed Race and Genetics / Meshell Sturgis and Ralina L. Joseph – 4. Listening to Racial Injustice / Dolores Inés Casillas and Jennifer Lynn Stoever – 5. Branding Athlete Activism / Jason Kido Lopez – 6. The Burden of Representation in Asian American Television / Peter X. Feng – 7. Indigenous Video Games / Jacqueline Land – 8. Applying Latina/o Critical Communication Theory to Anti-Blackness / Mari Castañeda – 9. Asian American Independent Media / Jun Okada – 10. Remediating Trans Visuality / Amy Villarejo – 11. Intersectional Distribution / Aymar Jean Christian – 12. Podcasting Blackness / Sarah Florini – 13. Black Twitter as Semi-Enclave / Raven Maragh-Lloyd – 14. Arab Americans and Participatory Culture / Sulafa Zidani – 15. Diaspora and Digital Media / Lia Wolock – 16. Disrupting News Media / Meredith D. Clark – 17. Latinx Audiences as Mosaic / Jillian M. Báez – 18. Media Activism in the Red Power Movement / Miranda J. Brady – 19. Black Gamers' Resistance / Kishonna L. Gray – 20. Cosmopolitan Fan Activism / Susan Noh.
Keywords: 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Indigeneity and Decolonial Seeing in Contemporary Art of Guatemala. - Cornejo, Kency (FUSE Magazine, 2013)
The magazine published its final issue in Winter 2013.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Coloniality at Large: Latin America and the Postcolonial Debate - Moraña, Mabel; Dussel, Enrique; Jáuregui, Carlos A. (Duke University Press, 2008)
Postcolonial theory has developed mainly in the U.S. academy, and it has focused chiefly on nineteenth-century and twentieth-century colonization and decolonization processes in Asia, Africa, the Middle East, and the Caribbean. Colonialism in Latin America originated centuries earlier, in the transoceanic adventures from which European modernity itself was born. Coloniality at Large brings together classic and new reflections on the theoretical implications of colonialism in Latin America. By pointing out its particular characteristics, the contributors highlight some of the philosophical and ideological blind spots of contemporary postcolonial theory as they offer a thorough analysis of that theory’s applicability to Latin America’s past and present. Written by internationally renowned scholars based in Latin America, the United States, and Europe, the essays reflect multiple disciplinary and ideological perspectives. Some are translated into English for the first time. The collection includes theoretical reflections, literary criticism, and historical and ethnographic case studies focused on Ecuador, Guatemala, Mexico, Brazil, the Andes, and the Caribbean. Contributors examine the relation of Marxist thought, dependency theory, and liberation theology to Latin Americans’ experience of and resistance to coloniality, and they emphasize the critique of Occidentalism and modernity as central to any understanding of the colonial project. Analyzing the many ways that Latin Americans have resisted imperialism and sought emancipation and sovereignty over several centuries, they delve into topics including violence, identity, otherness, memory, heterogeneity, and language. Contributors also explore Latin American intellectuals’ ambivalence about, or objections to, the “post” in postcolonial; to many, globalization and neoliberalism are the contemporary guises of colonialism in Latin America. Contributors : Arturo Arias, Gordon Brotherston, Santiago Castro-Gómez, Sara Castro-Klaren, Amaryll Chanady, Fernando Coronil, Román de la Campa, Enrique Dussel, Ramón Grosfoguel, Russell G. Hamilton, Peter Hulme, Carlos A. Jáuregui, Michael Löwy, Nelson Maldonado-Torres, José Antonio Mazzotti, Eduardo Mendieta, Walter D. Mignolo, Mario Roberto Morales, Mabel Moraña, Mary Louise Pratt, Aníbal Quijano, José Rabasa, Elzbieta Sklodowska, Catherine E. Walsh
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); _Nettoyé

Writing Art Histories From Below: A Decolonial Guanaca-Hood Perspective - Cornejo, Kency (Latin American and Latinx Visual Culture, 2019)
As a teenager during my first internship at the Los Angeles County Museum of Art, a diversity initiative for inner-city youth, the education curator enthusiastically asked, “Who here would like to be an art historian!?” Like all the other Black and Brown inner-city kids, I laughed inside. My response was not due to a lack of art appreciation; I grew up in a family of refugees who were all self-taught artists back home in El Salvador, who taught me to draw before I learned to read. Nor was my response rooted in apathy for creative expression, for I was involved in art and theater from my elementary through my high school years. Art was such a natural part of my life that the idea of studying it seemed wasteful to me. The truth was, the internship was one of two jobs I was working to financially help my family and pay for my first year of community college. Hidden even deeper, though, I believed the museum world was not my world. I was a guanaca (the appellative given to people from El Salvador) whose family fled war and remained invisible in mainstream US Latinx history and culture. I was also from the hood—in my case Compton, California, a city made notorious by gangsta rap and police brutality. I believed that people like me guarded the art on the museum walls, cleaned the floors and bathrooms for visitors, and served the food at the high-priced café. People who looked like me, who came from where I did, did not determine what art could be, nor could we afford to buy it. We certainly did not write the history of art, for if we had, we would see ourselves represented on the walls.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique centrale (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Section: 285 p. : ill. en coul. ; 25 cm.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé